2016
DOI: 10.1002/cyto.b.21374
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a flow cytometry‐based detection of γ‐H2AX, to measure DNA damage for clinical applications

Abstract: The FCM-γ-H2AX assay has sufficient analytical sensitivity and precision to measure levels of DNA damage and DNA repair for clinical purposes. © 2016 International Clinical Cytometry Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 31 publications
1
43
0
1
Order By: Relevance
“…The present results show that RES treatment to TRAMP cells caused significant cleavage of genomic DNA, which was accomplished by the expression of γ-H2A.X, an evolutionary conserved variant of histone H2A, has been identified as one of the key histones to undergo various post-translational modification in response to double stranded DNA breaks [90, 91]. DNA damage caused by radiation, UV light, or anti-cancer agents results in phosphorylation of Histone γ-H2A.X at ser-139 by PI3K-like kinases, including ATM, ATR, and DNA-PK [9294].…”
Section: Discussionmentioning
confidence: 96%
“…The present results show that RES treatment to TRAMP cells caused significant cleavage of genomic DNA, which was accomplished by the expression of γ-H2A.X, an evolutionary conserved variant of histone H2A, has been identified as one of the key histones to undergo various post-translational modification in response to double stranded DNA breaks [90, 91]. DNA damage caused by radiation, UV light, or anti-cancer agents results in phosphorylation of Histone γ-H2A.X at ser-139 by PI3K-like kinases, including ATM, ATR, and DNA-PK [9294].…”
Section: Discussionmentioning
confidence: 96%
“…The obtained results, with the FCM technique compared with those obtained with the validated method, demonstrated that the increased observed micronuclei percentage is perfectly comparable. Since the first protocol by N€ usse and Kramer published in 1984 (30) several researchers have proposed possible methods to measure DNA damage and to improve micronucleus analysis techniques or sample staining with ethidium bromide or Hoechst 33342 or ethidium monoazide (28,29,31,32). With respect to these methods, our procedure shows some advantages, such as the reduction of reagents and solutions used, the elimination of some procedural steps (i.e., ice refrigeration and staining activation under cold light lamp), which together lead to a simpler protocol with a significant reduction of costs and time required for sample staining.…”
Section: Discussionmentioning
confidence: 99%
“…H2AX phosphorylation was analyzed by flow cytometry analysis as described previously . Normalization of the γ‐H2AX values for a given dose were performed as follows: norm. S = SDay S×(mixcont.Day S/mixcont.Day N) where, S: sample γ‐H2AX MFI, norm.…”
Section: Methodsmentioning
confidence: 99%
“…Data analysis was performed using the BD Accuri C6 software as described previously (14). For cultured LCLs, the same gating strategy was used and only the cells in the G1 phase of the cell cycle were gated (according to their DNA content) and used for subsequent g-H2AX MFI measurement.…”
Section: Gating Strategymentioning
confidence: 99%
See 1 more Smart Citation